'I'm quite tired of people saying that I don't do enough or know anything': male hegemony and resistance in the context of women's online communication on doping. Issue 6 (23rd May 2022) - Sverkersson, Ellen
Abstract: This article aims to describe and analyse how female doping users discuss their doping practices and interact with other community members in an online forum. The article analyses women's narratives and how these relate to hegemonic gender configurations as regards doping and the doped female body. Analytically, the concept of hegemonic masculinity is used to approach notions of doped bodies and to investigate how women meet and possibly resist dominant gender hierarchies through doping use. The article utilises a netnographic approach to the research and data is based on discussion threads started by 45 women on a Swedish website and forum called Flashback. The results show how women entering the forum are encouraged to present their doping experiences and trajectories following a certain template through which lifestyle choices, diet, bodily ambitions, and more are explicitly addressed. Even though following the template and thereby using the correct and culturally accepted form for communication, the content is valued on the basis of hegemonic conceptualisations and understandings, which in itself results in women's rationales and goals often being downplayed by male commentators. Accordingly, the women's chances of establishing a space within the community, as fully accepted members, are limited. The women describe how their doping narratives are challenged based on their being women, in a way that has no equivalent for male members. In response to such criticism, some women decide to opt out of the forum, while others respond to the criticisms directed toward women, challenging the heteronormative and masculine hegemony.